(untitled) (Світ фінансів, 2017)
Лободіна З. М. Фінансові ресурси закладів охорони здоров’я дітей: реалії формування та перспективи зростання. Розглянуто моделі фінансового забезпечення закладів охорони здоров’я, їх недоліки та переваги. Проаналізовано фінансові ресурси закладів охорони здоров’я дітей та джерела їх формування. Запропоновано пропозиції щодо реформування фінансового забезпечення вищезгаданих закладів. Lobodina Z. Finances of health protection establishments for children: ways of their formation and prospects of extension. The article deals with the models of the financial maintenance of health protection establishments, their disadvantages and advantages are mentioned. Financial resources of establishments for children health protection and ways of their forming are analysed. Suggestions how to change financial maintenance of those establishments are proposed.